Prevalence of depression and cognitive impairment and their inter-relationship and association with quality of life among older stroke survivors: the findings of a national survey in China - Chee H Ng; Mu-rui Zheng; Gabor S Ungvari; Yu-Tao Xiang; Zhaohui Su; Yuan Feng; Pan Chen; Teris Cheung; Qinge Zhang (Stroke and Vascular Neurology)
Background Post-stroke depression (PSD) and post-stroke cognitive impairment (PSCI) are prevalent neuropsychiatric problems that are associated with high disability burden and low quality of life (QoL). This study explored the PSD-PSCI network, along with the interaction and association with QoL among Chinese older stroke survivors.Methods Data from the 2017–2018 wave of the Chinese Longitudinal Healthy Longevity Survey were obtained to investigate the inter-relationship between PSD and PSCI among older stroke survivors. Central and bridge symptoms within the PSD-PSCI network and their association with QoL were explored. Depressive symptoms, cognitive impairment and QoL were measured using the 10-item Center for Epidemiologic Studies Depression Scale (CESD-10), Mini-Mental State Examination and the WHO QoL-brief version, respectively.Results The prevalence of PSD and PSCI among older stroke survivors was 31.5% and 22.1%, respectively. In the PSD-PSCI network, ‘feeling blue/depressed’ (CESD3, strength: 1.117) and ‘Attention and calculation’ (At_C, strength: 0.972) were the most influential symptoms, while ‘Naming’ (Nam, bridge strength: 0.175) was the most significant bridge symptom. Notably, ‘Sleep disturbances’ (CESD10) had the strongest association with lower QoL.Conclusion This study revealed that both PSD and PSCI were prevalent among older stroke survivors. The key central and bridge symptoms in the PSD-PSCI network, along with those symptoms that negatively impact on QoL, should be prioritised in targeted interventions to enhance treatment outcomes in this population.